Human–Computer Interaction-Oriented African Literature and African Philosophy Appreciation - Wen, Jianlan; Piao, Yuming (Frontiers in Psychology, 2022)
African literature has played a major role in changing and shaping perceptions about African people and our way of life for the longest time. Unlike western cultures that are associated with advanced forms of writing, African literature is oral in nature, meaning it has to be recited and even performed. Although Africa has old tribal culture, African philosophy is a new and strange idea among us. While the problem of "universality" of African philosophy actually refers to the question of whether Africa has heckling of philosophy in the Western sense. Obviously, the philosophy bred by Africa's native culture must be acknowledged. Therefore, the Human-Computer Interaction-oriented (HCI-oriented) method is proposed to appreciate African literature and African philosophy. To begin with, a physical object of tablet-aid is designed, and depth camera is used to track the user's hand and tablet-aid and map them to the virtual scene respectively. Then, a tactile redirection method is proposed to meet the user's requirement of tactile consistency in Head-Mounted Display Virtual Reality (HMD-VR) environment. Finally, electroencephalogram (EEG) emotion recognition based on multi-scale convolution kernel Convolutional Neural Networks (CNN) is proposed to appreciate the reflection of African philosophy in African literature. The experimental results show that the proposed method has a strong immersion and good interactive experience in navigation, selection and manipulation. The proposed HCI method is not only easy to use, but also improves the interaction efficiency and accuracy during appreciation. In addition, the simulation of EEG emotion recognition reveals that the accuracy of emotion classification in 33-channel is 90.63%, almost close to the accuracy of the whole channel, and the proposed algorithm outperforms three baselines with respect to classification accuracy.